Development of the sa’ādah scale in the context of Indonesian Muslim adolescents - Ahmad Saifuddin; Santi Nuraini (Jurnal Psikologi, 2026)
Happiness is one of the factors that support mental health. However, not all theories of happiness are cross-culturally applicable. This condition causes happiness scales that use Western theories to be less relevant to groups of individuals with certain cultures and beliefs. Therefore, this study aims to develop a happiness scale from Al-Ghazali's concept (sa'ādah scale) in the context of Indonesian Muslim adolescents. After all items were validated by six raters (content validity coefficients ranged from 0.792 to 0.958), the sa'ādah scale was tested on 303 Muslim adolescents (female=170, male=133) in Central Java and Yogyakarta (Mage=20.759, SDage=1.383). The assumptions of unidimensionality and local independence were met. Of the total 32 items, one item was eliminated because the MNSQ outfit score was greater than 1.50. The point-to-measure correlation of the remaining 31 items was greater than 0.30 with satisfactory PSR and ISR. In addition, the correlation between the sa'ādah scale and the Tathmainn al-Qulūb Scale (TQS) (r=0.498; p<0.01) and the gratitude scale (r=0.909; p<0.01) was satisfactory. Thus, the sa'ādah scale was found to be of good quality. This sa'ādah scale can be used for research and measurement in efforts to achieve mental health among Muslim adolescents in Indonesia.